2019
DOI: 10.1016/j.nima.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a depleted monolithic pixel sensors in 150 nm CMOS technology for the ATLAS Inner Tracker upgrade

Abstract: This work presents a depleted monolithic active pixel sensor (DMAPS) prototype manufactured in the LFoundry 150 nm CMOS process. DMAPS exploit high voltage and/or high resistivity inclusion of modern CMOS technologies to achieve substantial depletion in the sensing volume. The described device, named LF-Monopix, was designed as a proof of concept of a fully monolithic sensor capable of operating in the environment of outer layers of the ATLAS Inner Tracker upgrade in 2025 for the High Luminosity Large Hadron C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…Moreover, previous e-TCT studies on test structures in LFoundry 150 nm CMOS [15] suggested that wafer thinning and back-side processing would result in an improvement in charge collection for irradiated thinned samples. By looking at their I-V curves (as depicted in Figure 3), the breakdown voltage was larger than 260 V independent of the sensor thickness or addition of metallization, in agreement with previous observations for unthinned samples [7,16]. I-V curves for back-side processed LF-Monopix samples of different thicknesses: 725 µm, 200 µm (with metallization) and 100 µm (without metallization).…”
Section: Leakage and Depletion After Thinningsupporting
confidence: 88%
“…Moreover, previous e-TCT studies on test structures in LFoundry 150 nm CMOS [15] suggested that wafer thinning and back-side processing would result in an improvement in charge collection for irradiated thinned samples. By looking at their I-V curves (as depicted in Figure 3), the breakdown voltage was larger than 260 V independent of the sensor thickness or addition of metallization, in agreement with previous observations for unthinned samples [7,16]. I-V curves for back-side processed LF-Monopix samples of different thicknesses: 725 µm, 200 µm (with metallization) and 100 µm (without metallization).…”
Section: Leakage and Depletion After Thinningsupporting
confidence: 88%